Agrobiodiversity and Feeding the World: More of the Same Will Result in More of the Same - Herforth, Anna; Johns, Timothy; Creed-Kanashiro, Hilary M.; Jones, Andrew D.; Khoury, Colin K.; Lang, Timothy; Maundu, Patrick; Powell, Bronwen; Reyes García, Victoria (MIT Press, 2019)
Food systems large and small around this planet are changing more quickly and more profoundly than ever before in human history. If the same processes and priorities continue, we can expect more of the same results: the last fifty years of a productionist paradigm have resulted in increased production of a small set of calorie-dense crops, increased calorie availability, and increased global homogeneity of diets, while environmental sustainability, human health, and equity issues remain unresolved. Food system sustainability is threatened by soil erosion, fertilizer pollution, water overuse, tropical forest degradation, climate change, and genetic uniformity in agricultural production. Meanwhile, access by all to healthy, diverse, and safe food choices is far from realized, and food-related noncommunicable diseases such as type 2 diabetes, obesity, and heart disease are now epidemics as the world increasingly partakes in a diet high in sugar, fat, and salt. There is reason for hope, as eaters on every continent are demanding healthier, more diverse, safer food. This chapter argues that agrobiodiversity will help to improve sustainability, equity, and nutrition outcomes in food systems. We briefl y review the current evidence on the linkages between agrobiodiversity and sustainability, equity, and human health and nutrition, differentiating between linkages at different geographical and temporal levels. We next identify research gaps in understanding the impact of agrobiodiversity on health. Because of the urgent need for action to create more sustainable, just, and nutritious food systems, we further propose tasks for the public sector as well as strategic alliances that support agrobiodiversity’s contributions to sustainability, equity, and human nutrition.